The Influence of EMI on Teacher Identity in a Colombian University - Corrales, Kathleen A.; Rey-Paba, Lourdes; Lombana-Coy, Jahir (Íkala, Revista de Lenguaje y Cultura, 2025)
English medium instruction (emi) is a growing initiative in Latin American higher education that requires instructors to adopt various roles. To understand this aspect better, this qualitative study explored how teaching emi classes affected the identity of a group of Colombian university instructors. Data gathered from semi-structured interviews and observations revealed that when teaching emi, instructors experienced a conflict among their professional, personal, and institutional identities, causing them to renegotiate their teaching self. The interplay of factors such as their perception as content experts, the need to provide language support, their pedagogical competence, their personal interest and proficiency in English, and their willingness to teach emi played a role in this conflict. These results highlight the need for instructors and institutions to face a possible identity reconfiguration to implement emi successfully. This article contributes to the theoretical and empirical understanding of teacher identity in emi in Latin America.